Myogenin, MyoD and IGF-I Regulate Muscle Mass but not Fiber-type Conversion during Resistance Training in Rats - Aguiar, A. F.; Vechetti-Júnior, I. J.; Alves de Souza, R. W.; Castan, E. P.; Milanezi-Aguiar, R. C.; Padovani, C. R.; Carvalho, R. F.; Silva, M.D P. (International Journal of Sports Medicine, 2013)
The purpose of this study was to test the hypothesis that skeletal muscle adaptations induced by long-term resistance training (RT) are associated with increased myogenic regulatory factors (MRF) and insulin-like growth factor-I (IGF-I) mRNA expression in rats skeletal muscle. Male Wistar rats were divided into 4 groups: 8-week control (C8), 8-week trained (T8), 12-week control (C12) and 12-week trained (T12). Trained rats were submitted to a progressive RT program (4 sets of 10–12 repetitions at 65–75% of the 1RM, 3 day/week), using a squat-training apparatus with electric stimulation. Muscle hypertrophy was determined by measurement of muscle fiber cross-sectional area (CSA) of the muscle fibers, and myogenin, MyoD and IGF-I mRNA expression were measured by RT-qPCR. A hypertrophic stabilization occurred between 8 and 12 weeks of RT (control-relative % area increase, T8: 29% vs. T12: 35%; p>0.05) and was accompanied by the stabilization of myogenin (control-relative % increase, T8: 44.8% vs. T12: 37.7%, p>0.05) and MyoD (control-relative % increase, T8: 22.9% vs. T12: 22.3%, p>0.05) mRNA expression and the return of IGF-I mRNA levels to the baseline (control-relative % increase, T8: 30.1% vs. T12: 1.5%, p<0.05). Moreover, there were significant positive correlations between the muscle fiber CSA and mRNA expression for MyoD (r=0.85, p=0.0001), myogenin (r=0.87, p=0.0001), and IGF-I (r=0.88, p=0.0001). The significant (p<0.05) increase in myogenin, MyoD and IGF-I mRNA expression after 8 weeks was not associated with changes in the fiber-type frequency. In addition, there was a type IIX/D-to-IIA fiber conversion at 12 weeks, even with the stabilization of MyoD and myogenin expression and the return of IGF-I levels to baseline. These results indicate a possible interaction between MRFs and IGF-I in the control of muscle hypertrophy during long-term RT and suggest that these factors are involved more in the regulation of muscle mass than in fiber-type conversion.
Keywords: muscle hypertrophy; fiber-type; strength training; myogenic regulatory factor; insulin-like growth factor